A Rare Cause of Fever of Unknown Origin: Reverse Shapiro’s Syndrome - Huseyin, Dag; Yelda, Turkmenoglu; Tugce, Aksu Uzunhan; Edebali, Erdogan; Ozge, Yapıcı Ugurlar; Habip, Gedik (Journal of Preventive Medicine And Care, 2019)
Reverse Shapiro’s syndrome is described as unexplained hyperthermia coexisting with agenesis of the corpus callosum. Its pathophysiology dwells on the role of dopaminergic hypersensitivity caused by hypothalamic dysfunction. Until now, only 5 cases have been described in the literature as reverse Shapiro’s syndrome. We present a case of a 6-month-old girl who is now the sixth patient described in the literature. A 6-month-old female patient was admitted to the pediatrics unit for fever of unknown origin. Her fever occurred 2-3 times a day on average between 38°C and 39.5°C, and lasted for 1-2 hours. The fever was not diurnal, and antipyretics or staying in an air-conditioned room had no effect. She also had 2 convulsions during her hospital stay. Cranial magnetic resonance imaging (MRI) was requested owing to the patient’s convulsion history and retarded development. The cranial MRI showed diffuse hypoplasia of the corpus callosum in the midline sagittal T2-weighted image. T1-weighted imaging showed hypointensity due to delayed myelination of the genu of the corpus callosum (Figure 2, white arrow), which should normally appear hyperintense like the posterior limb of the internal capsule. Although dopamine agonists and serotonin agonists are recommended for the treatment, the rate of response to medical treatment is very low. Our patient did not benefit from cyproheptadine and methyl prednisolone.
Keywords: Shapiro’s syndrome; hyperthermia; hypothermia; corpus callosum.